The effects and safety of anticoagulation or antiplatelet therapy following TIPS in cirrhotic patients with portal hypertension: A meta-analysis - Xu, Xiaotong; Fu, Yunlai; Jiang, Minjie; Wu, Muchen; Wu, Jing; Meng, Qinghua (Frontiers in Pharmacology, 2023)
Introduction: Transjugular intrahepatic portosystemic shunt (TIPS) is an effective way to improve portal hypertension, however, the role of anticoagulation or antiplatelet therapy following TIPS remains controversial. We conducted this study to evaluate the efficacy and safety of anticoagulation or antiplatelet therapy following TIPS. Methods: A literature search was conducted on anticoagulation or antiplatelet therapy after TIPS using Pubmed, Web of Science, EMBASE, and Cochrane. The retrieval period was from the earliest accessible date in the database to 31 October 2022. We collected information on the incidence of stent dysfunction, bleeding, hepatic encephalopathy, the new occurrence of portal vein thrombosis, and the survival rate. Stata was analyzed in RevMan. Results: 1. Four studies received anticoagulation or antiplatelet therapy after TIPS without control groups. According to the single-group rate meta-analysis, stent dysfunction occurred at 27% [95% CI (0.19, 0.38)], bleeding occurred at 21% [95% CI (0.14, 0.29)], new portal vein thrombosis occurred at 17% [(95%CI(0.04.0.71)], hepatic encephalopathy occurred at 47% [95%CI (0.34, 0.63)], and death occurred at 31% [95% CI (0.22, 0.42)]. 2. Eight studies, including 1025 patients, compared anticoagulation and antiplatelet therapy after TIPS to TIPS alone. In terms of stent dysfunction, bleeding, and hepatic encephalopathy, there were no significant differences between the two groups. The use of anticoagulation or antiplatelet therapy may result in a significant decrease in the incidence of new portal vein thrombosis and mortality over 1 year. Discussion: Anticoagulant or antiplatelet therapy may not improve the patency rate of TIPS, but may effectively prevent new portal vein thrombosis after TIPS. Following TIPS, the use of anticoagulants or antiplatelet drugs does not lead to an increase in bleeding or death.